Toxic effects of bisphenol A on goldfish gonad development and the possible pathway of BPA disturbance in female and male fish reproduction. (April 2019) - Wang, Qing; Yang, Huirong; Yang, Min; Yu, Yepin; Yan, Muting; Zhou, Lei; Liu, Xiaochun; Xiao, Shiqiang; Yang, Yan; Wang, Yuxin; Zheng, Leyun; Zhao, HuiHong; et al.
Abstract: Bisphenol A (BPA) is an abundant endocrine-disrupting compound that is found in the aquatic environment and has adverse effects on fish reproduction; however, the exact pathway of these impacts is unclear. In this study, the different effects of BPA on ovarian and testis development in goldfish ( Carassius auratus ) and the different mechanisms underlying these effects were investigated. The gonadosomatic index (GSI) and gonadal histology demonstrated that BPA diminished ovarian maturation in goldfish, which recovered after BPA treatment withdrawal. In males, BPA disrupted testis maturation, but this disruption could not be recovered after BPA treatment withdrawal. The hypothalamic-pituitary-gonad (HPG) axis-related genes sgnrh, fshβ and lhβ were significantly decreased in BPA-treated female fish, while no changes in sex steroid hormone levels and no TUNEL and PCNA staining were found in the ovary, suggesting that BPA may reduce ovarian maturation through the HPG axis. In male fish, TUNEL staining was found in 1 μg L −1 BPA-exposed germ cells and 50 and 500 μg L −1 BPA-exposed Leydig cells. Decreases in 11-KT levels were also found in 50 and 500 μg L −1 BPA-exposed fish, but BPA did not affect genes associated with the HPG axes. This result shows that BPA disrupts testis maturation through apoptosis of germ cells and Leydig cells, thus inducing decreases in 11-KT levels that disrupt spermatogenesis. Collectively, our findings provide insights into the molecular and cellular mechanisms underlying BPA disturbance of goldfish reproduction. Graphical abstract: BPA reduced ovarian maturation by affecting the HPG axis. BPA disrupted testis maturation through apoptosis of germ and Leydig cells, reduction of 11-KT plasma levels and altered spermatogenesis.Image 1 Highlights: BPA diminished ovarian maturation and this could be recovered after BPA treatment withdrawal. BPA disrupted testis maturation and this disruption cannot be recovered after BPA treatment withdrawals. BPA reduced ovarian maturation by affecting the HPG axis. BPA disrupted testis maturation through apoptosis of germ and Leydig cells, reduce androgen levels and altered spermatogenesis.